A DECISION MODEL FOR A QUALITY-ASSURED EPQ-BASED INTRA-SUPPLY CHAIN SYSTEM CONSIDERING OVERTIME OPTION - Lin, Hong-Dar; Chen, Yu-Ru Chen; Chiu, Victoria; Chiu, Yuan-Shyi Peter (Journal of Applied Engineering Science, 2019)
In order to gain competitive advantages, managers of present-day supply chain systems need to achieve critical operation goals, such as keeping flexible fabrication schedule, retaining product quality, maintaining timely delivery, and lowering overall operating costs. Inspired by these factors, this study developed a decision model for managers to investigate the joint impacts of quality-assured issues, overtime, and multi-shipment plan on optimal fabrication-shipment policy and on diverse system parameters of the economic production quantity (EPQ)-based supply chain system. An imperfect fabrication process producing perfect quality, repairable, and scrap items is assumed in the proposed system, along with assumptions of a flexible overtime schedule to partially expedite fabrication rate and a discontinuous multi-delivery policy for distributing end products. With a help from mathematical modeling and optimization method, the closed-form optimal fabrication-shipment policy is derived. A numerical example was employed to demonstrate applicability of our result and to expose critical managerial information of the system for supporting decision-making.